A Beam Search Method to Solve the Problem of Assignment Cells to Switches in a Cellular Mobile Network - Ribeiro, Cassilda Maria [UNESP]; Azevedo, Anibal Tavares [UNESP] (World Scientific and Engineering Acad and Soc, 2009)
Assigning cells to switches in a cellular mobile network is known as an NP-hard optimization problem. This means that the alternative for the solution of this type of problem is the use of heuristic methods, because they allow the discovery of a good solution in a very satisfactory computational time. This paper proposes a Beam Search method to solve the problem of assignment cell in cellular mobile networks. Some modifications in this algorithm are also presented, which allows its parallel application. Computational results obtained from several tests confirm the effectiveness of this approach and provide good solutions for large scale problems.
Keywords: Combinatorial Optimization; Assignment Problem; Beam Search Method; Cellular Network; Quadratic Integer Programming